The Relationship Between Vaginal Acidity (Ph) Level And The Incidence Of Leucorrhoea In Women Of Reproductive Age In The Coastal Area Of Bengkulu City - Saniyyah, Nabilah; Dewiani, Kurnia; Rachmawati, Ramya; Asmariyah; Yusanti, Linda (Universitas STRADA Indonesia, 2025)
Women of reproductive age (15-49 years) frequently experience leucorrhoea, influenced by various factors, including vaginal acidity (pH). This study aimed to investigate the relationship between vaginal pH levels and the incidence of leucorrhoea in women of reproductive age couples in the coastal areas of Bengkulu City. A quantitative survey method was employed, with 128 respondents selected using purposive sampling. Data were analyzed using the Chi-Square test. The results showed a significant correlation between vaginal pH and leucorrhoea category (p-value = 0.000 < 0.05). Most respondents had normal vaginal pH and experienced physiological leucorrhoea.